Toxin antitoxin system as an antimicrobial target for antibiotic resistant staphylococcus aureus - Ghafouryan, Sobhan (2014)
Antibiotic-resistant bacteria have become a global concern and new strategies to control pathogenic bacteria are urgently needed. Toxin antitoxin (TA) system is defined as a regulator system consist of toxin that neutralized by cognate antitoxin. In theory, activation of the toxin or inhibition of the antitoxin within a bacterial TA system could provide a potent new antibiotic therapy. TA systems can increase pathogen stress tolerance and certain TA loci have be characterized in a small number of Methicillin Resistant Staphylococcus aureus (MRSA), Vancomycin Resistant Enterococcus (VRE), E.coli, and Pesudomanas aeruginosa. Here it is determined the prevalence of TA system in a large number of independently isolated clinical isolates of antibiotic resistant S. aureus from diverse locations, then functionality of dominant TA system is evaluated and the antitoxin is subjected for silencing by antiMazE Peptide Nucleotide Acid (PNA) subsequently the suicide of bacteria by toxin is determined. To evaluate potential TA loci as therapeutic targets, it was screened the plasmid and chromosome sequences of 1000 clinical isolates of S. aureus from Milad hospital in Iran and 60 MRSA clinical isolates from Hospital Kuala Lumpur (HKL) in Malaysia for the presence of TA loci. Plasmid-borne MazEF TA loci were present in all tested, antibiotic resistant S. aureus strains in Iran and MRSA in Malaysia while when DNA were subjected as template, 21.2% of Milad hospital and 22.6% of HKL isolates were positive for MazEF TA system. In addition, plasmid transformation confirmed MazEF TA loci harboured on plasmid. Additionally, RT-PCR analysis revealed that the transcripts were produced from MazEF TA loci, suggesting that these loci are functional in the clinical isolates. Toxin transcript expression levels were increase when bacteria were grown under stressful conditions. Furthermore, cellular ATP levels are decreased consistent with MazF toxin expression and activity. The ATP results were confirmed by turbidity analysis. To activate toxin expression, it was targeted the MazE antitoxin mRNA using peptide nucleic acid (PNA) oligomers. The anti-MazE oligomers were bactericidal against drug-resistant S. aureus containing MazEF and did not inhibit strains lacking MazEF. Therefore, MazEF TA loci are widespread in drug-resistant strains of S.aureus and are plasmid-borne, and activation of toxin activity by silencing of the antitoxin gene provides a means to selectively kill drug resistant strains.